"Mr. Muhammad Zahid al-Pirakhderi Al-Shahoi and the Scholarly Efforts of His The Family of Sheikh Muhammad al-Khal as an Example" Descendants: - Abdullah, Dr. Aram Jalal (Sulaimani Journal for Humanities, 2023)
"There is no doubt that the source of knowledge and awareness came from the household of prophethood and the pure family members who Allah has cleansed from impurity and distinguished with perception, knowledge, and insight. Among those who are referred to in this field, shining like the moon in the sky of beneficence, is Mr. Muhammad Zahid al-Birakhdiri, who was a beacon for the people of guidance and a guide to the path of truth. Although he was born in Medina and grew up in a household of religion and ethics, his knowledge was like a flowing river, until he entered the land of Kurdistan. Since then and until now, his noble descendants have written in rational and transmitted sciences, excelling and benefiting. They taught and saved thousands of our kin from ignorance to knowledge. They did not confine their education to Kurdistan alone, but they ventured beyond Kurdistan and settled in the lands of Bilad al-Sham, Egypt, and the Hejaz, becoming leaders of those lands. Among the nobles who excelled in rational and transmitted sciences, and played a significant role in enlightening minds and hearts, was his grandson, Sheikh Muhammad al-Khal, who passed away in the year 1989 CE. Therefore, we find it fitting to shed light on the scholarly efforts of his family.